On some consequences of Mazur–Orlicz theorem to Hahn–Banach–Lagrange theorem. (3rd July 2018) - Grzybowski, Jerzy; Pallaschke, Diethard; Przybycień, Hubert; Urbański, Ryszard
Abstract : The paper examines different kinds of p -convexity of a function g which are sufficient for the existence of a linear functional such that in Theorem 1.13 of Simons in his monograph 'From Hahn–Banach to monotonicity', published in Springer lecture notes (2008). We replace sublinearity of p with convexity, the field with Dedekind vector lattice and present -convexity which is also necessary. In Theorem 4.7 we also generalize a result of MM. Neumann from 1991 published in Czech. Mathem. Journal Vol 41 on the Mazur–Orlicz theorem.